Sense and sensitivity – can an inaccurate test be better than no test at all? - Pugh, J; Wilkinson, D; Savulescu, J (BMJ, 2021)
The UK government has put Lateral Flow Antigen Tests (LFATs) at the forefront of its strategy to scale up testing in the coronavirus pandemic. However, evidence from a pilot trial using an LFAT to identify asymptomatic infections in the community suggests that the test missed over half of the positive cases in the tested population. This raises the question of whether it can it be ethical to use an inaccurate test to guide public health measures. We begin by explicating different dimensions of test accuracy (sensitivity, specificity, and predictive value), and why they matter morally, before highlighting key data from the Liverpool pilot. We argue that the poor sensitivity of the LFAT in this pilot suggests that there are important limitations to what we can expect these tests to achieve. A test with low sensitivity will provide false negative results, and in doing so generate the risk of false assurance and its attendant moral costs. However, we also suggest that the deployment of an insensitive but specific test could identify many asymptomatic carriers of the virus who are currently being missed under existing arrangements. Having outlined ways in which the costs of false reassurance could potentially be mitigated, we conclude that the use of an insensitive LFAT in mass testing may be ethical if (i) it is used predominantly to identify positive cases (ii) it is a cost-effective method of achieving that goal and (iii) if other public health tools can effectively prevent widespread false reassurance.